ANALISIS HUBUNGAN KAUSALITAS PERTUMBUHAN EKONOMI, KONSUMSI ENERGI, DAN EMISI CO2 DI INDONESIA PADA PERIODE 1980-2019 - Dwi Resti Pratiwi (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
Energy plays an important role in the growth of economic. On the other hand, the increase of economic growth will also trigger the occurrence of degradation of environmental quality derived from CO2 emissions. CO2 emissions are caused by oxidation process of fossil fuel energy. Many studies have attempted to look for causality between energy consumption, economic growth and CO2 emissions mainly on developing countries. This study therefore analyze the relationship between energy use, economic growth, and CO2 emissions in Indonesia during 1980-2019. It applies granger causality methods to examine the relationship between energy consumption, economic growth, and CO2 emission. The findings of this study indicate that there is no causality or unidirectional relationship between energy consumption and economic growth. There is no causal relationship between economic growth and CO2 emission and there is a unidirectional relationship from energy consumption to CO2 emission. Based on the result of analysis, it recommends that the government need to develop energy-efficient infrastructure, transform low carbon technologies aimed to reduce emissions and improve the use of renewable energy in all sectors.